Arts on prescription for community‐dwelling older people with a range of health and wellness needs. (21st October 2018) - Poulos, Roslyn G.; Marwood, Sally; Harkin, Damian; Opher, Simon; Clift, Stephen; Cole, Andrew M. D.; Rhee, Joel; Beilharz, Kirsty; Poulos, Christopher J.
Abstract: Published evidence for the role of participatory art in supporting health and well‐being is growing. The Arts on Prescription model is one vehicle by which participatory art can be delivered. Much of the focus of Arts on Prescription has been on the provision of creative activities for people with mental health needs. This Arts on Prescription program, however, targeted community‐dwelling older people with a wide range of health and wellness needs. Older people were referred to the program by their healthcare practitioner. Professional artists led courses in visual arts, photography, dance and movement, drama, singing, or music. Classes were held weekly for 8–10 weeks, with six to eight participants per class, and culminated with a showing of work or a performance. Program evaluation involved pre‐ and postcourse questionnaires, and focus groups and individual interviews. Evaluation data on 127 participants aged 65 years and older were available for analysis. We found that Arts on Prescription had a positive impact on participants. Quantitative findings revealed a statistically significant improvement in the Warwick–Edinburgh Mental Well‐being Scale (WEMWBS) as well as a statistically significant increase in the level of self‐reported creativity and frequency of creative activities. Qualitative findings indicated that the program provided challenging artistic activities which created a sense of purpose and direction, enabled personal growth and achievement, and empowered participants, in a setting which fostered the development of meaningful relationships with others. This evaluation adds to the evidence base in support of Arts on Prescription by expanding the application of the model to older people with a diverse range of health and wellness needs.